ITIL V3: Evaluation of IT Governance Gasindo Group - Nurul Lia Ocativa Devi Ariska; Wella Wella; Suryasari Suryasari (Universitas Islam Raden Rahmat, Malang, 2024)
This research was conducted at the Gasindo Group, especially in the enterprise resource planning system or commonly abbreviated as ERP. Researchers conducted research by measuring IT governance services using the ITIL V3 framework. The Department of Gasindo Group experienced data mismatches in controlling assets and trading activities due to errors in tube numbering registrations from various Departments. The research was conducted using the ITIL V3 framework in the Service Operation domain with 5 processes in it, namely Incident Management, Request Fulfillment, Event Management, Access Management and Problem Management. in this study only used three processes, namely problem management, access management and event management. The limitation of the distributed questionnaire adapts to the conditions that exist in the Gasindo Group. The percentage results obtained from problem management (71,1), access management (74,3) and event management stopped at level 1.